Analisis Hukum Islam Terhadap Pemberian Izin Poligami (Putusan Nomor 131/Pdt.G/2017/PA Maros) - Aswin, Muh; Hasibuddin, M.; Baedah, Said Syarifuddin Abu (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to examine the judge’s considerations in granting a polygamy permit under Islamic law in Decision Number 131/Pdt.G/2017/PA Maros at the Religious Court of Maros. It also seeks to understand how Islamic law responds to a husband’s request for polygamy based on specific reasons, and whether the court’s decision aligns with the principles of justice in Islam. This study employs a descriptive qualitative method. Data were collected through interviews with judges, observations at the Maros Religious Court, and documentation such as court decisions and other relevant legal documents. The research combines normative and empirical approaches to describe how the implementation of Islamic family law on polygamy is practiced in court. The results show that the judge granted the polygamy request based on several key considerations: the wife’s inability to bear children, the consent of the first wife, the husband’s financial readiness, and his willingness to act fairly. The decision was made in reference to Law Number 1 of 1974 on Marriage and Articles 56–57 of the Compilation of Islamic Law.